Realising participation and protection rights when working with groups of young survivors of childhood sexual violence: A decade of learning - Claire Cody; Silvie Bovarnick; Claire Soares (Child Protection and Practice)
Childhood sexual violence is a global problem that has far-reaching impacts on children, families and communities. Whilst there has been significant commitment and action to tackle this issue, research with young people consistently draws attention to gaps and limitations. Emerging research, and practice-based evidence, tells us that young survivors of childhood sexual violence hold essential knowledge and expertise about the impacts of, and solutions for addressing, this form of violence. Yet, despite widespread recognition that children and young people have a right to ‘be heard’, in practice there are limited examples where young survivors come together collectively to collaborate with professionals to inform and influence research, policy or practice interventions in this field. This discussion paper begins by reflecting on barriers to, and opportunities for, participatory engagement with young survivors. The article draws on a decade long international programme of work and shares three key elements that have helped ‘scaffold’ our participatory work with young survivors: forming the right partnerships; weighing up the potential risks and benefits of engagement; and putting in place support for all involved. In conclusion, we present potential ways forward, underscoring the importance of addressing structural barriers, the need for creativity, and the significance of support and training for those accompanying young people and facilitating their engagement in the future.